Low slag wire with excellent weldability

By controlling the cleanliness of components and non-metal inclusions in low-slag welding wire, combined with the alkali metal content in the surface treatment agent, the problem of Si and Mn-based slag residue after gas-protected arc welding is solved, and the electroplating coating performance and mechanical properties of the welding surface are improved.

JP2025511509AActive Publication Date: 2025-04-16KISWEL LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024553574
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-16
Filing Date
2023-04-13
Publication Date
2025-04-16
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

The prior art After gas protection arc welding, Si or Mn-based slag residues lead to a decrease in the performance of the electroplating coating, which in turn affects corrosion protection.

Method used

Low slag welding wire is used, and its components include C: 0.001-0.30%, Si: 0.001-0.10%, Mn: 0.50-3.00%, etc., by controlling the cleanliness of the non-metallic inclusions and the alkali metal content in the surface treatment agent, the formation of Si and Mn-based slag is reduced.

Benefits of technology

The performance and mechanical properties of the electroplating coating on the welding surface (such as tensile strength and ductility) are improved, while reducing the slag generation and accumulation of foreign matter in the spring line, ensuring good workingability of welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511509000001_ABST
    Figure 2025511509000001_ABST
Patent Text Reader

Abstract

One aspect of the present invention provides a low-slag wire with excellent weldability, which contains, in weight percent based on the total weight of the wire, 0.001-0.30% C, 0.001-0.10% Si, 0.50-3.00% Mn, 0.030% or less P, 0.020% or less S, 0.001-0.100% Ni, one or more of 0.50% or less Ti, 0.30% or less Al, 0.50% or less Nb, 0.10% or less V, and 0.10% or less Zr, one or more of 0.001-0.100%, 0.001-0.500% Mo, and 0.50% or less Cu, with the balance being Fe and unavoidable impurities.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a welding wire used for gas metal arc welding using a protective gas, and more particularly to a low slag wire having excellent weldability and capable of improving the electrodeposition paintability of the bead surface of a weld. [Background technology]

[0002] Generally, the method of protecting automotive parts from corrosive environments involves electrocoating after arc welding. However, when electrocoating is performed after welding, the electrocoating film is not formed on the welding slag, resulting in coating defects, which cause problems such as corrosion progressing from these defects.

[0003] Specifically, for components that require corrosion resistance, such as automobile chassis components, electrodeposition coating is performed after welding. If Si- and Mn-based slag remains on the surface of the weld bead during this electrodeposition coating, the electrodeposition coating property of that part will be poor.

[0004] As a result, the corrosion resistance of the areas where the Si and Mn-based slag remains is reduced.The reason why the electrodeposition paintability is reduced in the areas where the Si and Mn-based slag remains is because Si oxides and Mn oxides are insulators, so electricity cannot be passed through them during painting, and the paint does not adhere to the entire surface.

[0005] For this reason, there is a demand for welding materials that reduce the amount of Si- and Mn-based slag generated during gas-shielded arc welding and improve electrodeposition paintability. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention is intended to solve the problems of the prior art described above, and an object of the present invention is to provide a low slag wire with excellent weldability that can improve the electrodeposition paintability of the bead surface of a weld. [Means for solving the problem]

[0007] One aspect of the present invention provides a low-slag wire with excellent weldability, which contains, in weight percent based on the total weight of the wire, 0.001-0.30% C, 0.001-0.10% Si, 0.50-3.00% Mn, 0.030% or less P, 0.020% or less S, 0.001-0.100% Ni, one or more of 0.50% or less Ti, 0.30% or less Al, 0.50% or less Nb, 0.10% or less V, and 0.10% or less Zr, one or more of 0.001-0.100%, 0.001-0.500% Mo, and 0.50% or less Cu, with the balance being Fe and unavoidable impurities.

[0008] In one embodiment, the sum of cleanliness of non-metallic inclusions A, B, C, and D of the wire may be 2.5 or less, and A is a sulfide-based compound, B is an alumina-based compound, C is a silicate-based compound, and D is a globular oxide.

[0009] In one embodiment, the surface of the wire may be coated with a surface treatment agent containing, in weight percent relative to the total weight of the surface treatment agent, 0.20% to 0.30% of an alkali metal and 99.70 to 99.80% of a hydrocarbon compound having two functional groups selected from an ester group, a carboxylic acid group, and an alkane group.

[0010] In one embodiment, the alkali metal can be at least one element selected from the group consisting of sodium (Na), potassium (K), and calcium (Ca). Effect of the Invention

[0011] According to one aspect of the present invention, the component composition is appropriately controlled, so that it is possible to form a welded joint that has excellent electrodeposition paintability and mechanical properties (such as tensile strength and elongation). In addition, the cleanliness and the alkali metal content of the surface treatment agent are controlled, reducing the amount of spatter and the amount of foreign matter accumulated on the spring liner, ensuring excellent welding workability.

[0012] The effects of the present invention are not limited to the effects described above, but should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims. [Brief description of the drawings]

[0013] [Figure 1] FIG. 13 is a graph showing the amount of spatter generated depending on the degree of cleanliness. [Diagram 2] 1 is a photograph of nonmetallic inclusions in Example 2. [Diagram 3] 1 is a photograph of nonmetallic inclusions in Example 3. [Figure 4] 1 is a photograph of nonmetallic inclusions in Comparative Example 1. [Diagram 5] 1 is a photograph of nonmetallic inclusions in Comparative Example 2. [Figure 6] FIG. 11 is a graph showing the amount of spatter generation and the amount of foreign matter accumulated on a spring liner depending on the concentration of alkali metal. [Figure 7] FIG. 11 is a graph showing the amount of spatter generation and the amount of foreign matter accumulated on a spring liner depending on the concentration of alkali metal. [Figure 8] FIG. 8(a) is a photograph of the internal state of the spring liner of Example 10, and FIG. 8(b) is a photograph of the internal state of the spring liner of Comparative Example 14. [Figure 9] FIG. 9(a) is a photograph of the amount of sputtering generated in Example 10, FIG. 9(b) is a photograph of the amount of sputtering generated in Comparative Example 7, and FIG. 9(c) is a photograph of the amount of sputtering generated in Comparative Example 11. [Figure 10] FIG. 13 is a diagram showing the EDS analysis results of Example 9 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described below with reference to the accompanying drawings. However, the present invention may be embodied in various different forms and is therefore not limited to the embodiments described herein. In order to clearly explain the present invention in the drawings, parts that are not related to the description are omitted, and similar parts are designated by similar reference numerals throughout the specification.

[0015] Throughout the specification, when a part is described as being "connected" to another part, this includes not only the case where the part is "directly connected" to another part, but also the case where the part is "indirectly connected" to another part through another member in between. Furthermore, when a part is described as "including" a certain component, this means that the part can further include the other component, not excluding the other component, unless otherwise specified.

[0016] As used herein, terms including ordinal numbers, such as "first" or "second," may be used to describe various components or steps, but the components or steps should not be limited by the ordinal numbers. Terms including ordinal numbers should only be construed as being used to distinguish one component or step from another component or step.

[0017] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0018] The low slag wire having excellent weldability of the present invention is composed of, by weight percent, 0.001-0.30% C, 0.001-0.10% Si, 0.50-3.00% Mn, 0.030% or less P, 0.020% or less S, 0.001-0.100% Ni, one or more of 0.50% or less Ti, 0.30% or less Al, 0.50% or less Nb, 0.10% or less V, and 0.10% or less Zr, one or more of 0.001-0.100%, 0.001-0.500% Mo, and 0.50% or less Cu, with the balance being Fe and unavoidable impurities.

[0019] The compositional components of the low slag wire having excellent weldability according to the present invention and the reasons for limiting their contents will be explained. In the following, "%" refers to "% by weight."

[0020] <Carbon (C):0.001~0.30%> C has the effect of stabilizing the arc and refining the volume, and if the C content is less than 0.001%, the tensile strength of the deposited metal may not be obtained. Therefore, in the present invention, the C content is set to 0.001% or more.

[0021] On the other hand, if the C content exceeds 0.30%, the viscosity of the molten pool decreases, resulting in poor bead shape, and the deposited metal hardens, reducing crack resistance. Therefore, in the present invention, the C content is set to 0.30% or less.

[0022] <Silicon (Si): 0.001 to 0.10%> Silicon is actively added to ordinary welding wire as a deoxidizing element. Silicon also promotes the deoxidization of the molten pool during arc welding, improving the tensile strength of the deposited metal.

[0023] However, from the viewpoint of electrodeposition paintability, it is desirable to reduce insulating silicon oxide as much as possible. In other words, if the silicon content exceeds 0.10%, the amount of silicon-based slag generated increases, making it impossible to produce a weld metal with excellent electrodeposition paintability. Therefore, in the present invention, the Si content is set to 0.10% or less.

[0024] On the other hand, from the viewpoints of wire manufacturing costs and ensuring stability of the bead shape, the Si content is set to 0.001% or more.

[0025] <Manganese (Mn) 0.50~3.00%> Mn, like Si, is a deoxidizing element that promotes deoxidation of the molten pool during arc welding and improves the tensile strength of the weld metal. In the present invention, in order to maintain the Si content, which is the main deoxidizing element in the wire, at a very low level, the Mn content, which functions as a deoxidizer in the weld metal, is particularly controlled. Therefore, in the present invention, the Mn content is controlled to 3.00% or less.

[0026] On the other hand, Mn combines with S in steel to form MnS, which prevents the formation of FeS, a low melting point compound, and prevents the occurrence of high temperature cracks. It also refines pearlite and strengthens ferrite, thereby increasing the yield strength. Therefore, in the present invention, the Mn content is set to 0.50% or more in order to maintain the minimum yield strength.

[0027] <Phosphorus (P): 0.030% or less> P is an element that reduces the crack resistance of the weld metal, and the lower the P content in the wire, the more desirable it is. If the P content in the wire exceeds 0.030%, the required crack resistance cannot be obtained, and therefore, in the present invention, the P content is set to 0.030% or less.

[0028] <Sulfur (S): 0.020% or less> S is an element that has the effect of agglomerating slag. For example, if the amount of slag is kept constant and the S content in the wire is changed, the slag will agglomerate and increase in thickness as the S content increases, resulting in poor electrodeposition paintability. Therefore, the lower the S content, the better. If the S content in the wire exceeds 0.020%, it becomes difficult to uniformly form a thin slag on the weld metal, and there is a risk that the electrodeposition coating film will not be formed or that the slag will peel off entirely. Therefore, in the present invention, the S content is set to 0.020% or less.

[0029] <Nickel (Ni): 0.001 to 0.100%> Ni is an austenite stabilizing element and effectively contributes to improving impact resistance. If the Ni content is less than 0.001%, the strength of the deposited metal cannot be ensured. Therefore, in the present invention, the Ni content is set to 0.001% or more.

[0030] On the other hand, if the nickel content is high, NiS compounds are generated at grain boundaries during the welding process, and these compounds have a low melting point of 630°C and have a negative effect on high-temperature cracking and weldability. Therefore, in the present invention, the Ni content is set to 0.100% or less.

[0031] <Titanium (Ti): 0.50% or less> Titanium (Ti) has a high resistance to corrosion and functions as an arc stabilizer at high currents during welding. In addition, Ti is a slag-forming element. Therefore, in the present invention, the Ti content is set to 0.50% or less.

[0032] <Aluminum (Al): 0.30% or less> Although Al, together with Si, is useful as a strong deoxidizer, if added in large amounts to the deposited metal, it weakens the steel, therefore, in the present invention, the Al content is set to 0.30% or less.

[0033] <Niobium (Nb): 0.50% or less> Nb may be added to improve the quenching property of the welded portion and thereby improve the tensile strength, but if it is added in excess, the elongation of the welded portion decreases. Therefore, in the present invention, the Nb content is set to 0.5% or less.

[0034] <Vanadium (V): 0.10% or less> V may be added to improve the quenching property of the welded part and thereby the tensile strength, but if it is added in excess, the elongation of the welded part decreases. Therefore, in the present invention, the V content is set to 0.10% or less.

[0035] <Zirconium (Zr): 0.10% or less> Zr has a high affinity with nitrogen, sulfur, carbon, and hydrogen, and is often used to fix these elements. It is known that it can prevent the occurrence of white spots. Therefore, in the present invention, the Zr content is set to 0.10% or less.

[0036] <Chromium (Cr): 0.001~0.100%> Cr increases the strength and hardness of the deposited metal and facilitates the formation of carbides. It also improves corrosion resistance, heat resistance, and wear resistance. In order to maintain the appropriate strength, it is desirable to limit the content to 0.001% at the lower limit and 0.100% at the upper limit.

[0037] <Molybdenum (Mo): 0.001~0.500%> Mo may be added to improve the quenchability and tensile strength of the welded zone, but if it is added in excess, the elongation of the welded zone decreases. Therefore, in the present invention, the Mo content is set to 0.500% or less. On the other hand, in order to ensure the strength of the deposited metal, the Mo content is set to 0.001% or more.

[0038] <Copper (Cu): 0.50% or less> Cu increases the tensile strength and elastic limit of the deposited metal and increases the corrosion resistance, but it can cause cracks during rolling, so it is desirable to limit its content to an upper limit of 0.50%.

[0039] The remaining components are Fe and unavoidable impurities.

[0040] On the other hand, the above-mentioned wire composition of the present invention can be applied to a solid wire or a flux cored wire (metal cored wire). The wire of the present invention can also be used as a wire for SAW.

[0041] By using a wire satisfying the component composition of the present invention, it is possible to form a welded joint that has excellent electrodeposition paintability and mechanical properties (such as tensile strength and elongation).

[0042] Meanwhile, non-metallic inclusions in steel materials are a factor that affects slag or spatter during welding, and if there are large or numerous inclusions, they have a significant effect on the properties of the steel.

[0043] In view of this, the present invention aims to improve weldability by adjusting the cleanliness of non-metallic inclusions. Specifically, if the sum of the cleanliness of the nonmetallic inclusions exceeds 2.5, the amount of spatter increases sharply and weldability is impaired. Therefore, in the present invention, the sum of the cleanliness of the nonmetallic inclusions is set to 2.5 or less. Hereinafter, the present invention will be described in detail with reference to Example 1.

[0044] Example 1 Wires with good cleanliness and wires with poor cleanliness were manufactured, and welding was performed under the following conditions to examine the amount of spatter generated during welding.

[0045] A steel plate with a thickness of 12 mm, width of 10 cm, and length of 50 cm was placed in a box of 80 cm x 15 cm x 20 cm. The wire diameter was 1.2 mm, the setting current was 210 A, the setting voltage was 25 V, the welding speed was 40 cm / min, and the shielding gas was 80% Ar + 20% CO. 2 Downward welding was carried out under these conditions.

[0046] On the other hand, there are many methods for analyzing or evaluating inclusions. Representative methods include methods for measuring inclusions based on standards such as KS D 0204, JIS G 0555, ASTM E 45, and ISO 4967.

[0047] In this embodiment, based on ASTM E-45 Method A, diameter / 2 (mm) × length (mm) = 200 mm 2 The polished specimen is placed on the microscope and observed at a microscope magnification of 100x for specimens parallel to the longitudinal direction. While inspecting the entire specimen, compare it with standard diagrams of thin and thick series for each type of inclusion, and record the index of the standard diagram that matches the worst field of view.

[0048] Here, the non-metallic inclusions can be roughly classified into A, B, C, and D. In detail, A is a sulfide-based compound, B is an alumina-based compound, C is a silicate-based compound, and D is a globular oxide.

[0049] The amount of spatter was quantitatively measured by welding a 40 cm long bead for one minute and collecting the amount of spatter generated during welding.

[0050] FIG. 1 is a diagram showing the amount of spatter generation depending on cleanliness, FIG. 2 is a photograph of the non-metallic inclusions in Example 2, FIG. 3 is a photograph of the non-metallic inclusions in Example 3, FIG. 4 is a photograph of the non-metallic inclusions in Comparative Example 1, and FIG. 5 is a photograph of the non-metallic inclusions in Comparative Example 2.

[0051] As shown in FIGS. 1 to 5, in the case of Examples 1 to 6 in which the sum of the cleanliness of the nonmetallic inclusions A, B, C, and D was 2.5 or less, it was confirmed that the amount of spatter generation was reduced in all cases.

[0052] On the other hand, in the case of Comparative Examples 1 to 6 in which the sum of the cleanliness of the nonmetallic inclusions A, B, C, and D exceeds 2.5, it was confirmed that the amount of spatter generated increased by about 14 to 113% compared to the invention examples. Therefore, it can be seen that by controlling the sum of the cleanliness of the nonmetallic inclusions A, B, C, and D of the wire to 2.5 or less, the amount of spatter generated can be reduced and excellent welding workability can be ensured.

[0053] It has been found that, preferably, by controlling the sum of the cleanliness of non-metallic inclusions in the wire to 2.5 or less, the amount of spatter generated can be reduced and excellent welding workability can be ensured.

[0054] Generally, a gas metal arc welding wire is fed through a spring liner inside a welding torch via a feed roller, and then fed from the end of the torch to a base material for welding.

[0055] In order to perform stable welding, the welding wire must be fed to the weld at a constant speed. However, if foreign matter accumulates in the spring liner, friction occurs inside, hindering wire transfer and deteriorating weldability during long-term welding.

[0056] Therefore, the present invention is characterized in that a surface treatment agent containing an alkali metal is applied to the wire surface in order to reduce the amount of spatter generation and improve the arc stability. The alkali metal increases the arc stability and reduces the amount of spatter generation. The alkali metal preferably contains at least one element selected from the group consisting of Na, K, and Li.

[0057] Specifically, if the alkali metal content of the surface treatment agent is less than 0.20%, the amount of spatter increases and the welding workability deteriorates. Therefore, the alkali metal content of the surface treatment agent is 0.20% or more. Preferably, the alkali metal content of the surface treatment agent is 0.26% or more.

[0058] On the other hand, when the alkali metal content of the surface treatment agent exceeds 0.30%, the amount of spatter generation remains constant, but the amount of foreign matter accumulated on the spring liner increases sharply. Therefore, the alkali metal content of the surface treatment agent should be 0.30% or less.

[0059] Furthermore, the hydrocarbon compound having two functional groups selected from an ester group, a carboxylic acid group, and an alkane group may comprise 99.70 to 99.80% based on the total weight of the surface treatment agent. The hydrocarbon compound dissolves the metal salt in the surface treatment oil and forms a strong anti-rust film and a homogeneous liquid film on the wire surface.

[0060] Preferably, the surface treatment agent is applied to the wire surface in an amount of 0.03 to 0.60 g per 1 kg of wire.

[0061] The present invention will be described in detail below through Example 2. Example 2 Surface treatment agents with different alkali metal concentrations were applied to the surface of a wire containing 0.08% C, 0.10% Si, 1.5% Mn, 0.010% P, 0.020% S, 0.100% Ni, 0.100% Cr, with the balance being Fe and unavoidable impurities, which satisfies the composition range of the present invention, at 0.03 g per 1 kg of wire, and tests were conducted to evaluate the amount of spatter generation and the amount of foreign matter accumulation in the spring liner depending on the alkali metal concentration.

[0062] A steel plate with a thickness of 12 mm, width of 10 cm, and length of 50 cm was placed in a box of 80 cm x 15 cm x 20 cm. The wire diameter was 1.2 mm, the setting current was 210 A, the setting voltage was 25 V, the welding speed was 40 cm / min, and the shielding gas was 80% Ar + 20% CO. 2 Downward welding was carried out under these conditions.

[0063] The amount of spatter was quantitatively measured by welding a 40 cm long bead for one minute and collecting the amount of spatter generated during welding.

[0064] Figures 6 and 7 are figures showing the amount of spatter generation and the amount of foreign matter accumulation in the spring liner depending on the alkali metal concentration, Figure 8(a) is a photograph of the internal state of the spring liner of Example 10, Figure 8(b) is a photograph of the internal state of the spring liner of Comparative Example 14, Figure 9(a) is a photograph of the amount of spatter generation in Example 10, Figure 9(b) is a photograph of the amount of spatter generation in Comparative Example 7, Figure 9(c) is a photograph of the amount of spatter generation in Comparative Example 11, and Figure 10 is a diagram showing the results of EDS analysis of Example 9.

[0065] As shown in Figures 6 to 10, in the case of Examples 7 to 12 in which a surface treatment agent with an alkali metal content of 0.20% to 0.30% was applied, the amount of spatter generation was reduced while at the same time the amount of foreign matter accumulated on the spring liner was reduced.

[0066] On the other hand, in Comparative Examples 9 to 11 in which the surface treatment agent containing less than 0.20% of alkali metal was applied, the amount of foreign matter accumulated on the spring liner was reduced, but it was confirmed that the amount of spatter generation increased.

[0067] In Comparative Examples 12 to 14, in which a surface treatment agent containing more than 0.30% alkali metal was applied, the amount of spatter generation was reduced, but it was confirmed that the amount of accumulation of foreign matter on the spring liner increased rapidly.

[0068] Therefore, it can be seen that by coating the wire surface with a surface treatment agent containing 0.20% or more and 0.30% or less of alkali metal and 99.70 to 99.80% of a hydrocarbon compound having two functional groups selected from an ester group, a carboxylic acid group, and an alkane group, the amount of spatter generated and the amount of foreign matter accumulated on the spring liner can be reduced, ensuring excellent welding workability.

[0069] The above description of the present invention is for illustrative purposes only, and those skilled in the art will understand that the present invention can be easily modified into other specific forms without changing the technical idea or essential features of the present invention. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and are not limiting. For example, each component described in a single form may be implemented in a distributed form, and similarly, components described as being distributed may be implemented in a combined form.

[0070] The scope of the present invention is defined by the following claims, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be construed as being included in the scope of the present invention.

Claims

1. Percentage by weight based on the total weight of the wire: C: 0.001 to 0.30%; Si: 0.001 to 0.10%, Mn: 0.50 to 3.00%; P: 0.030% or less; S: 0.020% or less; Ni: 0.001 to 0.100%; One or more of Ti: 0.50% or less, Al: 0.30% or less, Nb: 0.50% or less, V: 0.10% or less, and Zr: 0.10% or less; One or more of Cr: 0.001 to 0.100%, Mo: 0.001 to 0.500%, and Cu: 0.50% or less; The remainder is Fe and unavoidable impurities.

2. The sum of the cleanliness of the non-metallic inclusions A, B, C, and D in the wire is 2.5 or less; 2. The low slag wire having excellent weldability according to claim 1, wherein A is a sulfide-based compound, B is an alumina-based compound, C is a silicate-based compound, and D is a globular oxide.

3. Percentage by weight based on the total weight of the surface treatment agent, 2. The low slag wire having excellent weldability according to claim 1, characterized in that the surface of the wire is coated with a surface treatment agent containing 0.20% to 0.30% of an alkali metal and 99.70% to 99.80% of a hydrocarbon compound having two functional groups selected from an ester group, a carboxylic acid group, and an alkane group.

4. 4. The low slag wire having excellent weldability according to claim 3, wherein the alkali metal is at least one element selected from the group consisting of sodium (Na), potassium (K), and calcium (Ca).

Citation Information

Patent Citations

  • Low hydrogen type coated electrode

    JP1998263883A

  • Flux cored wire for gas-shielded arc welding for low alloy heat resistant steel

    JP2003019595A

  • Flux cored wire for electroslag welding

    JP2005271032A

  • Two-electrode large heat input submerged arc welding method

    JP2006212676A

  • Surface treating oil, and solid wire for gas shielded arc welding

    JP2006326686A